(untitled) (Desenvolvimento em Questão, 2025)
In the daily practice of organizational and social activities, Social Management evolves and is enriched by the contribution of various forms of knowledge that go beyond academic technical expertise, also including community experiences and lived realities. This study aims to highlight the use of participatory methodologies as an alternative to strengthen and consolidate the theoretical assumptions of Social Management. By adopting such methodologies, which foster collective action and shared learning, participants are granted access to decision-making processes, resulting in the empowerment and capacity building of both the actors involved and the organizations. These approaches align with the fundamental principles of Social Management, which advocate for active engagement in public spheres toward common goals and individual emancipation. Thus, the crucial importance of collaboration and effective participation in the design of sustainable and inclusive social solutions is underscored. In this sense, this paper contributes to the field of Social Management by proposing the use of participatory methodologies as tools to strengthen and consolidate its theoretical assumptions. The research highlights the Emancipatory Rapid Participatory Diagnosis (ERPD) as an effective example of a methodology aligned with the principles of Social Management, emphasizing participation, dialogue, and emancipation. Through the analysis of ERPD, the paper demonstrates how the use of participatory methods, which value individuals’ voices and experiences, strengthens Social Management and promotes civic autonomy, essential aspects for the enhancement of the common good.